Kinerja Lingkungan, Biaya Lingkungan Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Dengan Corporate Social Responsibility Sebagai Variabel Intervening - Farhan Habib Siregar; Syahyunan Syahyunan; Zuwina Miraza (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
company size on financial performance through corporate social responsibility either directly or indirectly in mining companies listed on the Indonesia Stock Exchange. This research is causal associative research and the type of data used is quantitative data. The data used is obtained from the company's financial statements that have been audited on the Indonesia Stock Exchange during the study period. The analytical method used is descriptive analysis, testing the assumptions of the hypothesis test model. The population of this study are mining companies for the 2017-2020 period, which totaled 50 companies. The sample in this study amounted to 15 companies. The results of this study indicate that environmental performance has a positive and significant effect on company performance, environmental costs have a negative and significant effect on company performance, company size has a negative and insignificant effect on company performance, corporate social responsibility has a negative and insignificant effect on company performance, and environmental performance has a negative effect. and not significant to the company's performance through corporate social responsibility, environmental costs have a positive and insignificant effect, the size of environmental companies has a negative and insignificant effect on company performance through corporate social responsibility.